Rodas de conversa: uma proposta para aprimorar a prática docente em educação física escolar - Marques, André Eduardo (Universidade Federal de São Carlos, 2013)
The inclusion of students with disabilities in regular education is a reality and Physical Education is one of the responsible subjects for this process to occur. Physical Education and disabled people have suffered segregation and exclusion and have been facing great difficulties in the paradigm of inclusion. Hence, some questions arise: How is the process of inclusion of disabled students in Physical Education classes happening? What are the difficulties of the Physical Education teacher when facing the inclusion of these students? Such questions conducted the research, which is aimed at: investigating (alongside teachers from local elementary schools in a city in the State of São Paulo in classrooms with disabled students in the inclusion process) how the inclusion of these students is happening; verifying the difficulties encountered in professional practice; then, sensitizing Physical Education teachers, using group chats to share experiences and knowledge related to daily classes. The adopted methodology for this study was a descriptive qualitative research. Semi-structured interviews were performed with principals of municipal schools, resource room teachers and Physical Education teachers in classrooms with disabled students; observation and recording of physical education classes were also carried, as group chats with teachers, who then exchanged experiences and knowledge. The interviews were recorded, transcribed and analyzed in the form of meaning units. It was possible to notice that the Department of Education (through the Division of Special Education) and school directors know that much has to be done so that the school becomes a place of valuing differences. Thus, we are able to suggest improvements and discuss problems related to needs the school system presents.
Keywords: Educação especial; Educação física escolar; Inclusão; Rodas de conversa; Special Education; Physical education; Inclusion, Chat groups; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL